Tectonomagmatic settings of Jurassic granitoids in the Sanandaj-Sirjan Zone, Iran: A review - Karimpour, Mohammad Hassan; Shirdashtzadeh, Nargess; Sadeghi, Martiya (Geologos, 2022)
The present paper discusses the geochemical affinities, origin and ages of Jurassic granitoids of the Sanandaj-Sirjan Zone (SaSZ) in the eastern part of the Zagros Thrust Zone. A multidisciplinary, integrated approach was carried out using existing granitoid geochemical data (major, trace, rare earth element and isotopes) and knowledge of the regional geology (geodynamic and metamorphic setting), coupled with geophysical data (magnetic susceptibility) from granitoids in the SaSZ. We re-interpret and re-classify the Jurassic granitoids of this zone into three main genetic groups: S-type, I-type and A-type subduction-related ones. In the central to southern part of the Sanandaj-Sirjan zone (between Hamadan and Sirjan), S-type magmatism appeared between 178 and 160 Ma during the Cimmerian orogeny, due to continental collision. To the north of the Sanandaj-Sirjan zone (between Sanandaj and Ghorveh), I-type and A-type magmatism occurred between 158 and 145 Ma. This heterogenic tectonomagmatic system along the SaSZ suggests a heterogenic subcontinental lithospheric mantle, resulting in two Jurassic tectonomagmatic zones of (1) the Sanandaj-Ghorveh Zone and (2) the Hamadan-Sirjan Zone.